PENGARUH MOTIVASI DAN KEPUASAN KERJA KARYAWAN: MODERATION KEPEMIMPINAN TRANSFORMASIONAL - I Nengah Aristana; Anak Agung Ketut Sri Asih; Putu Agus Eka Rismawan (Journal Research of Management, 2023)
This research aims to determine the effect of intrinsic motivation and extrinsic motivation on employee job satisfaction in the hotel business. This research design uses a quantitative approach where the data collection tool uses a questionnaire distributed to 261 four-star hotel employees. Research data was analyzed using Smart PLS 3.2.3. The findings of this research indicate that intrinsic motivation and extrinsic motivation have a positive and significant effect on employee job satisfaction. Furthermore, transformational leadership does not play a moderating role in the relationship between intrinsic motivation and employee job satisfaction. However, transformational leadership acts as a moderator of the relationship between extrinsic motivation and employee job satisfaction.